Election of Honorary Members of the Russian Mineralogical Society from 1917 to 1937 - Ivan Yu. Matveev (Вестник Северного (Арктического) федерального университета: Серия «Гуманитарные и социальные науки»)
The period of 1917–1937 includes three stages in the development of Russian science: the decline in scientific research caused by socio-political changes and the Civil War, the establishment of Soviet power and the sovietization of science, and the tightening party control over science from the late 1920s onwards. Honorary membership has always been one of the forms of membership in a scientific organization, and the Russian Mineralogical Society was no exception. Its honorary members were persons who had made a major contribution to the development of both Russian and world science. Before the February Revolution of 1917, honorary membership could be granted to non-scientists who had contributed to the organizational development of the Society. Election of honorary members had always been a rare event for the organization, one exception being year 1916, when the Society granted 45 memberships to both Russian and foreign scientists. In 1917, before the February Revolution, three more honorary members were elected. From then on, this practice followed a downward trend. In 1921, only one honorary member was elected, and until 1937 no more honorary memberships were granted. Using the example of the Russian Mineralogical Society, one can observe how external circumstances influenced the work of a scientific organization in terms of electing honorary members during the period under study. The research is based on the minutes of the Russian Mineralogical Society published in the Papers of the Russian Mineralogical Society, as well as on archival data from the Central State Archives of Saint-Petersburg.